2001
DOI: 10.1128/jcm.39.2.696-704.2001
|View full text |Cite
|
Sign up to set email alerts
|

Typing and Subtyping Influenza Virus Using DNA Microarrays and Multiplex Reverse Transcriptase PCR

Abstract: A model DNA microarray has been prepared and shown to facilitate typing and subtyping of human influenza A and B viruses. Reverse transcriptase PCR was used to prepare cDNAs encoding ϳ500-bp influenza virus gene fragments, which were then cloned, sequenced, reamplified, and spotted to form a glass-bound microarray. These target DNAs included multiple fragments of the hemagglutinin, neuraminidase, and matrix protein genes. Cy3-or Cy5-labeled fluorescent probes were then hybridized to these target DNAs, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(101 citation statements)
references
References 27 publications
1
99
0
1
Order By: Relevance
“…Finally, molecular characterization studies showed that no molecular adaptive changes occurred and almost identical viruses infected humans and swine. There were only minor differences between human and swine pH1N1 isolates, which is likely, given the natural mutation rate of influenza virus both in vitro and in vivo [16,17].…”
Section: Discussionmentioning
confidence: 96%
“…Finally, molecular characterization studies showed that no molecular adaptive changes occurred and almost identical viruses infected humans and swine. There were only minor differences between human and swine pH1N1 isolates, which is likely, given the natural mutation rate of influenza virus both in vitro and in vivo [16,17].…”
Section: Discussionmentioning
confidence: 96%
“…Microarrays are the new diagnostics tools for identification and quick subtyping of influenza viruses. For this low-density oligonucleotide microarrays containing limited number of highly multiplexed unique conserved genome "signatures" sequences as probes are used [9][10][11][12][13]. These microarrays are used to detect both influenza A and B viruses as well as various subtypes of influenza A viruses on the basis of three gene targets the HA, NA and M (Matrix) gene segments [6,10,14,15].…”
Section: Microarray Chips For Identification and Sub Typing Of Influementioning
confidence: 99%
“…The study could identify 3 unknown influenza viruses; however the technique suffered from high degree of mismatches (approx. 14%) [13]. In order to resolve this problem smaller oligonucleotide based arrays were designed containing conserved viral genome for greater specificity.…”
Section: Microarray Designing and Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCR method was used to amplify and label the reference gene. 13 This reaction mixture (total volume: 100 ml) consisted of 10 ml of 103 PCR buffer, 4 ml of dNTP (mixed with Cy3-29-deoxyuridine 59-triphosphate [dUTP]), j 1 ml of Taq DNA recombinant polymerase (rTaq), k 2 ml of forward primer, 2 ml of Cy3-labeled reverse primer, 1 ml of GAPDH plasmid, and 80 ml of DEPC-treated sterile double distilled H 2 O. The thermal cycler conditions were 5 min of predenaturation at 95uC, followed by 35 cycles of 94uC for 45 sec, 53uC for 45 sec, and 72uC for 60 sec; and a final 10-min extension at 72uC.…”
Section: Preparation Of Labeled Cdna Samplesmentioning
confidence: 99%